HUBUNGAN KOMITMEN ORGANISASI DAN IKLIM ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN RUMAH SAKIT SWASTA ISLAM MALANG - Nurul Asfiah (Manajemen Bisnis, 2011)
Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah MalangE-mail: asfi.1918@gmail.comABSTRACTThe aims of research are to know the condition and to examine the relationship between organizationalcommitment and climate to the employee’ job satisfactions. The research was conducted in IslamicPrivate Hospital Malang and include 140 peoples as respondents. Questionnaires used as an instrumentfor collecting data. The analyses method uses Rank scale and product moment correlation. Theresults of research show that the organizational commitment is in good conditions as well as organizationalclimate. Whereas, the conditions of employee’ job satisfaction is in the high level satisfied. Basedon the product moment show that the relationship between both organizational commitment and climateto the employee’ job satisfaction are in the strong level. It means that all employees in Islamic PrivateHospital are having strong organizational commitment and feeling satisfaction when they are working.It is also the organizational climate, it supports to make employee enjoy their working.Keywords: organizational commitment and organizational climate, employee’ job satisfaction, IslamicPrivate Hospital Malang.